MEMBANGUN HOTSPOT AREA DENGAN PEMANFAATAN APLIKASI MIKHMON UNTUK HAK AKSES PENGGUNA INTERNET DI DESA BOJONEGARA, SERANG, BANTEN - Afrasim Yusta; Andri Cahayadi; Penny Hendriyati (CV. Multi Kreasi Media, 2022)
The need for the internet along with various needs in supporting various community activities has become an important thing, as well as for people located in the village of Bojonegara where the availability of internet that implements a wireless internet network or can be called a wireless network with the aim of expanding coverage throughout the surrounding areas, so that with the exixtence of this wireless network the mobility of internet user is getting higher, making hotspot users experience a tremendous increase the problem is how bojonegara village builds a computer network using Wifi, what is the purpose of bojonegara village building an internet network, how to open a new business by utilizing the internet network (technology), how to benefit from the advancement of internet network technology that has been build by one of the residents there. In this community service, we try to install a network that can be used for all resident of Bojonegara village by utilizing the Wifi network by building a hotspot area that is installed, one of which is by using a hotspot voucher using the Mikhmon application partner collaboration with a tower triange at the central point of the server and planted at several point in Bojonegara Village. The result obtained are that the network is a great opportunity for the community in Bojonegara village to open a home industry-based entrepreneur facilitated by the village through iMicro.